Program Pembelajaran di Sekolah Inklusi - Saputra, Riva Ady; Anam, Muhammad Syaroful (Proceedings Series on Social Sciences & Humanities, 2025)
Education is a basic right of every Indonesian citizen, including those with special needs. As in Law Number 20 of 2003 in Article 5 Paragraph 1, that every citizen has the same right to obtain quality education. This is reinforced by the National Regulation as the basis for the implementation of inclusive education, namely Article 31 of the 1945 Constitution concerning the right to receive education for all. Indonesian people without exception. Law No. 20 of 2003 concerning the National Education System, Law No. 23 of 2002 concerning Child Protection. Government Regulation No. 13 of 2020 concerning appropriate accommodation for Students with Disabilities. PP No. 13 of 2020 article 5 states that providing accommodation is one form of preparation for education and education personnel. The provisions of the Government of the Ministry of Education and Culture in article 6 of the Minister of Education and Culture No. 70 of 2009 state that inclusive education must be implemented by every region in Indonesia. The article states: 1) the district or city government claims that inclusive education is implemented with the needs of students, 2) the district or city government claims that inclusive education resources are available inclusive education in inclusive education, 3) the city government and provincial government provide assistance for the continuity of educational resources.